Design considerations is cross layer framework for cognitive UWB - Norazizah Mohd. Aripin, author; Norulhusna Ahmad, author; Rozeha A. Rashid, 1968-, author; Norsheila Fisal, author; International Joint Journal Conference in Computer Electronics and Electrical (2009 : Finland) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL